Controlled trial of speech therapy versus oxprenolol for stammering. Issue 6290 (22nd August 1981) - Rustin, L; Kuhr, A; Cook, P J; James, I M
Abstract : In a controlled trial of treatment for stammering under stress oxprenolol (40 mg) compared with placebo was assessed in a double-blind manner over two days, six weeks apart, in 31 stammerers before and after speech therapy. The trial design also allowed six weeks of intensive speech therapy, using a slowed-speech and relaxation technique, to be compared with not treatment and assessed single-blind. Oxprenolol produced a significant fall in pulse rate and systolic blood pressure but no overall change in performance either before or after speech therapy. Intensive speech therapy produced a highly significant improvement in the global performance of untrained subjects (p less than 0.001) and a significant reduction in the number (p less than 0.001) and duration (p less than 0.001) of blocks. Maintenance speech therapy tended to produce further improvement in trained subjects. Speech therapy is apparently an effective treatment for stammering, whereas oxprenolol appears to be of no value when given routinely; oxprenolol may be of value, however, in very stressful conditions.